Promoción de los museos Indio Guaranga y la Guitarra en el Cantón Guaranda, Provincia Bolívar. año 2024. - Poaquiza Poaquiza, Lisandra Gabriela (2025)
The aim of this research was to develop strategies to improve the promotion of museums in the city of Guaranda, located in the Guaranda canton, Bolívar province. This study focused on the problem of the limited dissemination of these institutions. To achieve the proposed goals, a mixed research approach was adopted, combining qualitative and quantitative methods. The research design included the analysis of documents, as well as the conduct of interviews and surveys to obtain key information on the current situation of museums in the city. First, an exhaustive review of bibliographic sources was carried out, such as blogs, academic articles, theses and databases such as Scopus and Google Scholar, complemented by interviews for contrast. Subsequently, field work was used to carry out surveys which allowed us to know the different preferences that tourists have when it comes to tourism. These surveys provided quantitative and qualitative information, thus enhancing the study of the results obtained. Finally, with the results obtained, it is concluded that the museums of the city of Guaranda have insufficient management in the promotion of their own activities, which is why this study contributes to identifying new promotional strategies for their development.